Mecanismo de citotoxicidade do anticorpo monoclonal A4, que reconhece protocaderina β13, em células tumorais murinas e humanas - Santos, Luana Cheven Perbore dos [UNIFESP] (2010)
Malignant melanoma is a highly metastatic skin cancer which arises from malignant transformation of melanocytes. Incidence of melanoma has been increasing in the last decades, becoming a major public health problem in many countries. Monoclonal antibodies (mAbs) have been used in cancer immunotherapy as tools for diagnosis, monitoring and treatment of tumors. The discovery of new therapeutic targets for mAbs in tumor cells, and the establishment of their cytotoxic mechanisms might significantly improve the possibilities and efficacy of cancer treatments. Previously in our research group, Dobroff and collaborators (2002) produced a mAb, named A4, which was cytotoxicity in vitro against B16F10-Nex2 murine melanoma cells and some human tumor cell lines. This effect was independent of complement, although enhanced by it. MAb A4 decreased B16F10-Nex2 murine melanoma development in vivo, significantly increasing animal survival. This mAb recognizes Protocadherin â13 (PCDHâ13) at tumor cell surface, a protein that belongs to the cadherin superfamily, and preliminary results suggested that mAb A4/PCDHâ13 interaction leads tumor cell to apoptosis (Dobroff et. al., 2010, in press). In the present work, mAb A4 reactivity with murine melanoma cells and several human tumor cell lines was verified by Chemoluminescent ELISA and Indirect Immunofluorescence assays. Pcdhâ13 mRNA expression was detected by nonquantitative RT-PCR and PCDHâ13 protein expression by Immunoblotting assay. Only PCDHâ13-expressing tumor cells were susceptible to mAb A4 cytotoxicity. MAb A4 was cytotoxic in vitro to murine melanoma and to human tumor cell lines, including melanoma, colon carcinoma, cervical uterine epithelioid carcinoma and glioblastoma. MAb A4 had no activity against breast carcinoma cell lines and murine immortalized melanocytes melan A, which do not express PCDHâ13. MAb A4 interaction with B16F10-Nex2.1 cells in vitro triggered mAb A4 endocytosis, rapid reduction of free cytoplasmic â-catenin and TCF-4 concentrations, redistribution of â-catenin to cell periphery, caspases-9, -3, and -6 activation, phosphatidilserine translocation to cell membrane, chromatin condensation and internucleossomal DNA fragmentation, confirming the induction of mitochondrialdependent apoptosis in that tumor cell line. Additionally, mAb A4 induced overproduction of oxygen reactive species, which can amplify the apoptotic process. The inhibition of â-catenin signaling suggests that signaling pathways that regulate cell survival and growth were inhibited by mAb A4 interaction with its target on the cell surface. Transmission electron microscopy images revealed the presence of autophagosomes, suggesting the simultaneous induction of autophagy and apoptosis by mAb A4. We conclude that mAb A4 may represent a new therapeutic agent with antitumor activity against murine and human tumors. PCDHâ13 is a potential melanoma marker. MAb A4 interaction with PCDHâ13 induced cell death through inhibition of b-catenin/TCF-4 signaling pathway and induction of the apoptosis intrinsic pathway. The autophagic process might be also implicated in mAb A4 cytotoxic effect.